Preparation method of phosphorus-doped hard carbon composite material for sodium battery

By preparing phosphorus-doped hard carbon composite materials, the existing hard carbon anode materials have poor conductivity and low reversible capacity in sodium batteries, and the high capacity, good conductivity and long cycle stability of the material are achieved.

CN119612496APending Publication Date: 2025-03-14FUJIAN XFH NEW ENERGY MATERIALS CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510070145.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing hard carbon anode materials have poor conductivity, low reversible capacity, low first-time efficiency and poor long-cycle stability in sodium batteries.

Method used

By preparing phosphorus-doped hard carbon composite materials, pre-oxidation treatment was performed using biomass raw materials, then mechanically mixed with phosphorus dopant and asphalt, and graphene and carbon nanotubes were formed by vapor deposition, and finally pickling and purification were performed.

Benefits of technology

It significantly improves the capacity and conductivity of the material, improves the first-time efficiency and long cycle stability, and provides good reversible capacity at ultra-high currents, showing excellent rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005245468860000111
    Figure BDA0005245468860000111
Patent Text Reader

Abstract

The invention discloses a preparation method of a phosphorus-doped hard carbon composite material for a sodium battery. The preparation method comprises the following steps: preparing a hard carbon precursor, preparing a phosphorus-doped precursor, preparing a catalyst precursor, preparing a hard carbon composite material, and carrying out pickling purification. Through pre-oxidation treatment on the biomass raw material, oxygen-containing free radicals can be introduced, the structural disorder can be improved, the sodium storage space and the capacity can be improved, phosphorus elements are uniformly distributed into the hard carbon material through a vapor deposition method, meanwhile, graphene and carbon nanotubes are formed in the material, closed pores are increased, the sodium storage space is improved, and the performance of the hard carbon material is improved. According to the present invention, the ion transmission path is shortened, the sodium ion transmission is accelerated, the capacity and the conductivity of the material are enhanced, the material is coated with the amorphous carbon formed by the asphalt, such that the phosphorus expansion can be inhibited, the contact with the electrolyte can be avoided, the capacity and the first effect can be improved, and the phosphorus and the coating layer can be re-distributed while the asphalt coating is performed so as to form the small amount of the phosphorus fiber crystal; and the conductivity and the capacity are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of electrode materials, and in particular to a method for preparing a phosphorus-doped hard carbon composite material for a sodium battery. Background Art

[0002] With the rapid development of the new energy industry, the market demand for lithium-ion batteries has surged, but the global reserves of lithium are relatively scarce and will not be able to meet future demand. The working principle of sodium-ion batteries is similar to that of lithium-ion batteries, but the reserves of sodium are more abundant, so the research and development of sodium-ion batteries has been rapid and has attracted much attention. However, since the atomic radius of sodium ions is larger than that of lithium, it is difficult for them to enter the layers of traditional lithium battery negative electrode materials such as graphite, while amorphous carbon such as hard carbon has a larger interlayer spacing than graphite and can store sodium ions, making it an ideal negative electrode material for sodium-ion batteries. Therefore, it has become urgent to find a method for preparing hard carbon negative electrode materials.

[0003] At present, the hard carbon process route is long, the product indicators are strict, the structure-activity relationship is relatively complex, and although the hard carbon has good sodium storage performance, it still has defects such as poor conductivity, low reversible capacity, low initial efficiency and poor long-cycle stability. In order to improve these defects and optimize electrochemical performance, it is a very effective way to compound hard carbon with other materials with excellent conductive properties, modify the morphology, and form a conductive network and porous structure. However, how to achieve this uniform, effective and low-cost material composite is still a problem. For this reason, it is necessary to improve the existing hard carbon negative electrode materials. Summary of the invention

[0004] In view of this, the present invention aims to address the deficiencies in the prior art, and its main purpose is to provide a method for preparing a phosphorus-doped hard carbon composite material for sodium batteries, which can effectively solve the problems of poor conductivity, low reversible capacity, low initial efficiency and poor long-cycle stability of existing hard carbon negative electrode materials.

[0005] To achieve the above purpose, the present invention adopts the following technical solutions:

[0006] A method for preparing a phosphorus-doped hard carbon composite material for a sodium battery comprises the following steps:

[0007] (1) Preparing a hard carbon precursor: selecting a biomass raw material, heating it to 200-400°C in an air atmosphere at a heating rate of 2-10°C / min, keeping it warm for 24-72 hours, and cooling it naturally to obtain a pre-oxidized hard carbon precursor;

[0008] (2) Preparing a phosphorus-doped precursor: mechanically mixing the pre-oxidized hard carbon precursor obtained in step (1) with a phosphorus-containing dopant, and after mixing evenly, heating the mixture to 400-600°C at a heating rate of 2-10°C / min in a vacuum atmosphere and keeping the mixture warm for 2-8 hours, and then mechanically mixing the mixture with asphalt after naturally cooling, and after mixing evenly, heating the mixture to 400-600°C at a heating rate of 2-10°C / min under the protection of an inert gas and keeping the mixture warm for 2-8 hours, and then heating the mixture to 800-1000°C and keeping the mixture warm for 2-8 hours to obtain a phosphorus-doped precursor; wherein the mass of the phosphorus-containing dopant is 2-8% of the mass of the pre-oxidized hard carbon precursor, and the mass of the asphalt is 1-10% of the mass of the pre-oxidized hard carbon precursor;

[0009] (3) preparing a catalyst precursor: adding the phosphorus-doped precursor obtained in step (2) to deionized water, adding a transition metal salt, the mass of which is 0.01-0.08% of the phosphorus-doped precursor, stirring for 6-72 hours, evaporating to dryness at 80° C., heating to 200-400° C. in an air atmosphere, and keeping the temperature for 1-3 hours to obtain a catalyst precursor;

[0010] (4) preparing a hard carbon composite material: heating the catalyst precursor obtained in step (3) to 600-1200° C. in a mixed atmosphere of an inert gas and a carbon source gas for vapor deposition, keeping the temperature for 10-120 minutes, cooling naturally, and grinding thoroughly to obtain a hard carbon composite material;

[0011] (5) Acid washing and purification: The hard carbon composite material obtained in step (4) is immersed in an acidic solution for 10-30 minutes, and then the immersed hard carbon composite material is washed with water until the pH is neutral to obtain a phosphorus-doped hard carbon composite material.

[0012] As a preferred solution, the D50 of the biomass raw material is 5-11 μm.

[0013] As a preferred embodiment, the biomass raw material is at least one of coconut shell, straw and starch.

[0014] As a preferred embodiment, the phosphorus-containing dopant is at least one of red phosphorus, sodium phosphate and ammonium phosphate.

[0015] As a preferred embodiment, the transition metal salt is at least one of copper nitrate, nickel nitrate, cobalt nitrate and iron nitrate.

[0016] As a preferred embodiment, the carbon source gas is at least one of benzene, toluene, xylene, ethanol, methane, ethylene and acetylene.

[0017] Compared with the prior art, the present invention has obvious advantages and beneficial effects. Specifically, it can be seen from the above technical solution that:

[0018] By pre-oxidizing the biomass raw materials, oxygen-containing free radicals can be introduced to increase the disorder of the structure, which is beneficial to increase the sodium storage space and capacity. The phosphorus element is evenly distributed in the hard carbon material through vapor deposition, and graphene and carbon nanotubes are formed in the material at the same time, which increases the formation of closed pores, increases the sodium storage space, shortens the ion transmission path, and accelerates the kinetics of sodium ion transmission. The capacity and conductivity of the material are generally enhanced. The amorphous carbon formed by asphalt is then coated to inhibit the expansion of phosphorus and avoid its contact with the electrolyte, thereby improving the capacity and first efficiency. In addition, while coating with asphalt, phosphorus and the coating layer can be redistributed to form a small amount of phosphorus fiber crystals, which is beneficial to improve conductivity and capacity, so that the phosphorus-doped hard carbon composite material has a unique porous structure and conductive network, which makes the material have good first efficiency and long cycle stability. The synergistic effect of multiple materials enhances the electrochemical performance, and can provide good reversible capacity under ultra-high current, showing excellent rate performance.

[0019] In order to more clearly illustrate the structural features and effects of the present invention, the present invention is described in detail below in conjunction with specific embodiments. DETAILED DESCRIPTION

[0020] The present invention discloses a method for preparing a phosphorus-doped hard carbon composite material for a sodium battery, comprising the following steps:

[0021] (1) Preparing a hard carbon precursor: selecting a biomass raw material, heating it to 200-400°C in an air atmosphere at a heating rate of 2-10°C / min, keeping it warm for 24-72 hours, and naturally cooling it to obtain a pre-oxidized hard carbon precursor; the biomass raw material is at least one of coconut shell, straw, and starch, and the D50 of the biomass raw material is 5-11 μm.

[0022] (2) Preparing a phosphorus-doped precursor: mechanically mixing the pre-oxidized hard carbon precursor obtained in step (1) with a phosphorus-containing dopant, and after mixing evenly, heating the mixture to 400-600°C at a heating rate of 2-10°C / min in a vacuum atmosphere and keeping the mixture warm for 2-8 hours, and then naturally cooling the mixture and mechanically mixing the mixture with asphalt, and after mixing evenly, heating the mixture to 400-600°C at a heating rate of 2-10°C / min under the protection of an inert gas and keeping the mixture warm for 2-8 hours, and then heating the mixture to 800-1000°C and keeping the mixture warm for 2-8 hours to obtain a phosphorus-doped precursor; wherein the mass of the phosphorus-containing dopant is 2-8% of the mass of the pre-oxidized hard carbon precursor, and the mass of the asphalt is 1-10% of the mass of the pre-oxidized hard carbon precursor; and the phosphorus-containing dopant is at least one of red phosphorus, sodium phosphate, and ammonium phosphate.

[0023] (3) preparing a catalyst precursor: adding the phosphorus-doped precursor obtained in step (2) into deionized water, adding a transition metal salt, the mass of which is 0.01-0.08% of the phosphorus-doped precursor, stirring for 6-72 hours, evaporating to dryness at 80° C., heating to 200-400° C. in an air atmosphere, and keeping warm for 1-3 hours to obtain a catalyst precursor; the transition metal salt is at least one of copper nitrate, nickel nitrate, cobalt nitrate, and iron nitrate.

[0024] (4) Preparation of hard carbon composite materials: The catalyst precursor obtained in step (3) is heated to 600-1200°C in a mixed atmosphere of inert gas and carbon source gas for vapor deposition, kept warm for 10-120 minutes, naturally cooled, and then fully ground to obtain a hard carbon composite material; the carbon source gas is at least one of benzene, toluene, xylene, ethanol, methane, ethylene, and acetylene.

[0025] (5) Acid washing and purification: The hard carbon composite material obtained in step (4) is immersed in an acidic solution for 10-30 minutes, and then the immersed hard carbon composite material is washed with water until the pH is neutral to obtain a phosphorus-doped hard carbon composite material.

[0026] The following is a detailed description with reference to a number of embodiments.

[0027] Example 1

[0028] (1) Preparation of hard carbon precursor: Select biomass raw material, heat it to 300°C in air atmosphere at a heating rate of 2°C / min, keep it warm for 36 hours, and naturally cool it to obtain a pre-oxidized hard carbon precursor; the biomass raw material is coconut shell, and the D50 of the biomass raw material is 5-11 μm.

[0029] (2) Preparation of a phosphorus-doped precursor: Mechanically mix the pre-oxidized hard carbon precursor obtained in step (1) with a phosphorus-containing dopant. After mixing evenly, heat the mixture to 500°C at a heating rate of 2°C / min in a vacuum atmosphere and keep the mixture warm for 6 hours. After natural cooling, mechanically mix the mixture with asphalt. After mixing evenly, heat the mixture to 500°C at a heating rate of 2°C / min under the protection of an inert gas and keep the mixture warm for 8 hours, then heat the mixture to 900°C and keep the mixture warm for 8 hours to obtain a phosphorus-doped precursor. The mass of the phosphorus-containing dopant is 3% of the mass of the pre-oxidized hard carbon precursor, and the mass of the asphalt is 3% of the mass of the pre-oxidized hard carbon precursor. The phosphorus-containing dopant is red phosphorus.

[0030] (3) Preparation of a catalyst precursor: The phosphorus-doped precursor obtained in step (2) is added to deionized water, and a transition metal salt is added, wherein the mass of the transition metal salt is 0.01% of the phosphorus-doped precursor. After stirring for 60 hours, the mixture is evaporated to dryness at 80° C., heated to 200° C. in an air atmosphere, and kept warm for 2 hours to obtain a catalyst precursor; the transition metal salt is copper nitrate.

[0031] (4) Preparation of hard carbon composite materials: The catalyst precursor obtained in step (3) is heated to 1000°C for vapor deposition in a mixed atmosphere of an inert gas and a carbon source gas, kept warm for 100 minutes, cooled naturally, and then fully ground to obtain a hard carbon composite material; the carbon source gas is benzene.

[0032] (5) Acid washing and purification: The hard carbon composite material obtained in step (4) is immersed in an acidic solution for 10 minutes, and then the immersed hard carbon composite material is washed with water until the pH is neutral to obtain a phosphorus-doped hard carbon composite material.

[0033] Example 2

[0034] (1) Preparing a hard carbon precursor: selecting a biomass raw material, heating it to 300°C in an air atmosphere at a heating rate of 10°C / min, keeping it warm for 48 hours, and naturally cooling it to obtain a pre-oxidized hard carbon precursor; the biomass raw material is straw, and the D50 of the biomass raw material is 5-11 μm.

[0035] (2) Preparation of a phosphorus-doped precursor: Mechanically mix the pre-oxidized hard carbon precursor obtained in step (1) with a phosphorus-containing dopant. After mixing evenly, heat the mixture to 300°C at a heating rate of 10°C / min in a vacuum atmosphere and keep the mixture warm for 6 hours. After natural cooling, mechanically mix the mixture with asphalt. After mixing evenly, heat the mixture to 600°C at a heating rate of 2°C / min under the protection of an inert gas and keep the mixture warm for 4 hours, then heat the mixture to 900°C and keep the mixture warm for 2 hours to obtain a phosphorus-doped precursor. The mass of the phosphorus-containing dopant is 2% of the mass of the pre-oxidized hard carbon precursor, and the mass of the asphalt is 10% of the mass of the pre-oxidized hard carbon precursor. The phosphorus-containing dopant is sodium phosphate.

[0036] (3) Preparation of a catalyst precursor: The phosphorus-doped precursor obtained in step (2) is added to deionized water, and a transition metal salt is added, wherein the mass of the transition metal salt is 0.08% of the phosphorus-doped precursor. After stirring for 22 hours, the mixture is evaporated to dryness at 80° C., heated to 300° C. in an air atmosphere, and kept warm for 1 hour to obtain a catalyst precursor; the transition metal salt is nickel nitrate.

[0037] (4) Preparation of hard carbon composite materials: The catalyst precursor obtained in step (3) is heated to 600°C for vapor deposition in a mixed atmosphere of an inert gas and a carbon source gas, kept warm for 60 minutes, cooled naturally, and then fully ground to obtain a hard carbon composite material; the carbon source gas is toluene.

[0038] (5) Acid washing and purification: The hard carbon composite material obtained in step (4) is immersed in an acidic solution for 30 minutes, and then the immersed hard carbon composite material is washed with water until the pH is neutral to obtain a phosphorus-doped hard carbon composite material.

[0039] Example 3

[0040] (1) Preparing a hard carbon precursor: A biomass raw material is selected, and the temperature is increased to 200°C in an air atmosphere at a heating rate of 5°C / min, and the temperature is kept for 60 hours. After natural cooling, a pre-oxidized hard carbon precursor is obtained; the biomass raw material is starch, and the D50 of the biomass raw material is 5-11 μm.

[0041] (2) Preparation of a phosphorus-doped precursor: Mechanically mix the pre-oxidized hard carbon precursor obtained in step (1) with a phosphorus-containing dopant. After mixing evenly, heat the mixture to 600°C at a heating rate of 6°C / min in a vacuum atmosphere and keep the mixture warm for 8 hours. After natural cooling, mechanically mix the mixture with asphalt. After mixing evenly, heat the mixture to 500°C at a heating rate of 10°C / min under the protection of an inert gas and keep the mixture warm for 5 hours, then heat the mixture to 800°C and keep the mixture warm for 3 hours to obtain a phosphorus-doped precursor. The mass of the phosphorus-containing dopant is 4% of the mass of the pre-oxidized hard carbon precursor, and the mass of the asphalt is 6.5% of the mass of the pre-oxidized hard carbon precursor. The phosphorus-containing dopant is ammonium phosphate.

[0042] (3) Preparation of a catalyst precursor: The phosphorus-doped precursor obtained in step (2) is added to deionized water, and a transition metal salt is added, wherein the mass of the transition metal salt is 0.05% of the phosphorus-doped precursor. After stirring for 6 hours, the mixture is evaporated to dryness at 80° C., heated to 250° C. in an air atmosphere, and kept warm for 1 hour to obtain a catalyst precursor; the transition metal salt is cobalt nitrate.

[0043] (4) Preparation of hard carbon composite materials: The catalyst precursor obtained in step (3) is heated to 1200°C for vapor deposition in a mixed atmosphere of an inert gas and a carbon source gas, kept warm for 100 minutes, cooled naturally, and then fully ground to obtain a hard carbon composite material; the carbon source gas is xylene.

[0044] (5) Acid washing and purification: The hard carbon composite material obtained in step (4) is immersed in an acidic solution for 25 minutes, and then the immersed hard carbon composite material is washed with water until the pH is neutral to obtain a phosphorus-doped hard carbon composite material.

[0045] Example 4

[0046] (1) Preparation of hard carbon precursor: Select biomass raw material, heat it to 400°C in air atmosphere at a heating rate of 8°C / min. Keep it warm for 24 hours, and cool it naturally to obtain a pre-oxidized hard carbon precursor; the biomass raw material is a mixture of coconut shell and straw, and the D50 of the biomass raw material is 5-11 μm.

[0047] (2) Preparation of a phosphorus-doped precursor: Mechanically mix the pre-oxidized hard carbon precursor obtained in step (1) with a phosphorus-containing dopant. After mixing evenly, heat the mixture to 500°C at a heating rate of 7°C / min in a vacuum atmosphere and keep the mixture warm for 6 hours. After natural cooling, mechanically mix the mixture with asphalt. After mixing evenly, heat the mixture to 400°C at a heating rate of 8°C / min under the protection of an inert gas and keep the mixture warm for 2 hours, then heat the mixture to 1000°C and keep the mixture warm for 5 hours to obtain a phosphorus-doped precursor. The mass of the phosphorus-containing dopant is 8% of the mass of the pre-oxidized hard carbon precursor, and the mass of the asphalt is 2% of the mass of the pre-oxidized hard carbon precursor. The phosphorus-containing dopant is sodium phosphate.

[0048] (3) Preparation of a catalyst precursor: The phosphorus-doped precursor obtained in step (2) is added to deionized water, and a transition metal salt is added, wherein the mass of the transition metal salt is 0.03% of the phosphorus-doped precursor. After stirring for 72 hours, the mixture is evaporated to dryness at 80° C., heated to 300° C. in an air atmosphere, and kept warm for 3 hours to obtain a catalyst precursor; the transition metal salt is ferric nitrate.

[0049] (4) Preparation of hard carbon composite materials: The catalyst precursor obtained in step (3) is heated to 700°C for vapor deposition in a mixed atmosphere of inert gas and carbon source gas, kept warm for 10 minutes, cooled naturally, and then fully ground to obtain a hard carbon composite material; the carbon source gas is a mixed gas of ethanol and methane.

[0050] (5) Acid washing and purification: The hard carbon composite material obtained in step (4) is immersed in an acidic solution for 15 minutes, and then the immersed hard carbon composite material is washed with water until the pH is neutral to obtain a phosphorus-doped hard carbon composite material.

[0051] Example 5

[0052] (1) Preparing a hard carbon precursor: selecting a biomass raw material, heating it to 360°C in an air atmosphere at a heating rate of 7°C / min, keeping it warm for 72 hours, and naturally cooling it to obtain a pre-oxidized hard carbon precursor; the biomass raw material is a mixture of straw and starch, and the D50 of the biomass raw material is 5-11 μm.

[0053] (2) Preparation of a phosphorus-doped precursor: Mechanically mix the pre-oxidized hard carbon precursor obtained in step (1) with a phosphorus-containing dopant. After mixing evenly, heat the mixture to 400°C at a heating rate of 5°C / min in a vacuum atmosphere and keep the mixture warm for 7 hours. After natural cooling, mechanically mix the mixture with asphalt. After mixing evenly, heat the mixture to 500°C at a heating rate of 4°C / min under the protection of an inert gas and keep the mixture warm for 7 hours, then heat the mixture to 900°C and keep the mixture warm for 3 hours to obtain a phosphorus-doped precursor. The mass of the phosphorus-containing dopant is 4% of the mass of the pre-oxidized hard carbon precursor, and the mass of the asphalt is 5% of the mass of the pre-oxidized hard carbon precursor. The phosphorus-containing dopant is ammonium phosphate.

[0054] (3) Preparation of catalyst precursor: The phosphorus-doped precursor obtained in step (2) is added to deionized water, and a transition metal salt is added, wherein the mass of the transition metal salt is 0.06% of the phosphorus-doped precursor. After stirring for 24 hours, the mixture is evaporated to dryness at 80° C., heated to 280° C. in an air atmosphere, and kept warm for 2.5 hours to obtain a catalyst precursor; the transition metal salts are nickel nitrate and cobalt nitrate.

[0055] (4) Preparation of hard carbon composite materials: The catalyst precursor obtained in step (3) is heated to 880°C for vapor deposition in a mixed atmosphere of inert gas and carbon source gas, kept warm for 100 minutes, cooled naturally, and then fully ground to obtain a hard carbon composite material; the carbon source gas is ethylene.

[0056] (5) Acid washing and purification: The hard carbon composite material obtained in step (4) is immersed in an acidic solution for 18 minutes, and then the immersed hard carbon composite material is washed with water until the pH is neutral to obtain a phosphorus-doped hard carbon composite material.

[0057] Example 6

[0058] (1) Preparation of hard carbon precursor: Select biomass raw material, heat it to 200°C in air atmosphere at a heating rate of 5°C / min. Keep it warm for 48 hours, and cool it naturally to obtain a pre-oxidized hard carbon precursor; the biomass raw material is coconut shell, and the D50 of the biomass raw material is 5-11 μm.

[0059] (2) Preparation of a phosphorus-doped precursor: Mechanically mix the pre-oxidized hard carbon precursor obtained in step (1) with a phosphorus-containing dopant. After mixing evenly, heat the mixture to 500°C at a heating rate of 4°C / min in a vacuum atmosphere and keep the mixture warm for 6 hours. After natural cooling, mechanically mix the mixture with asphalt. After mixing evenly, heat the mixture to 600°C at a heating rate of 6°C / min under the protection of an inert gas and keep the mixture warm for 7 hours, then heat the mixture to 900°C and keep the mixture warm for 4 hours to obtain a phosphorus-doped precursor. The mass of the phosphorus-containing dopant is 6% of the mass of the pre-oxidized hard carbon precursor, and the mass of the asphalt is 1% of the mass of the pre-oxidized hard carbon precursor. The phosphorus-containing dopant is sodium phosphate and ammonium phosphate.

[0060] (3) Preparation of catalyst precursor: adding the phosphorus-doped precursor obtained in step (2) into deionized water, adding transition metal salt, the mass of which is 0.03% of the phosphorus-doped precursor, stirring for 60 hours, evaporating at 80°C, heating to 400°C in an air atmosphere, and keeping warm for 3 hours to obtain a catalyst precursor; the transition metal salt is copper nitrate and iron nitrate.

[0061] (4) Preparation of hard carbon composite materials: The catalyst precursor obtained in step (3) is heated to 1100°C for vapor deposition in a mixed atmosphere of an inert gas and a carbon source gas, kept warm for 120 minutes, cooled naturally, and then fully ground to obtain a hard carbon composite material; the carbon source gas is acetylene.

[0062] (5) Acid washing and purification: The hard carbon composite material obtained in step (4) is immersed in an acidic solution for 25 minutes, and then the immersed hard carbon composite material is washed with water until the pH is neutral to obtain a phosphorus-doped hard carbon composite material.

[0063] Performance tests were performed on the above multiple embodiments, and the test results are shown in Table 1.

[0064]

[0065] Table 1

[0066] It can be clearly seen from Table 1 that the hard carbon composite materials prepared in Examples 1-6 have a small particle size and a large specific surface area. They have a loose and porous structure, which is beneficial to increasing the sodium storage space, increasing the capacity, shortening the ion transmission path, and enhancing the conductivity of the material. At the same time, they also have a large first discharge capacity and a high first discharge efficiency. After 800 cycles, they can still maintain an extremely high cycle retention rate of 88%. It can be seen that the hard carbon composite material prepared by the preparation method of the present invention has good first efficiency and long cycle stability, can provide good reversible capacity under ultra-high current, and exhibits excellent rate performance.

[0067] The above description is only a preferred embodiment of the present invention and does not limit the technical scope of the present invention. Therefore, any slight modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a phosphorus-doped hard carbon composite material for sodium batteries, characterized in that: The following steps are included: (1) Preparing a hard carbon precursor: selecting a biomass raw material, heating it to 200-400°C in an air atmosphere at a heating rate of 2-10°C / min, keeping it warm for 24-72 hours, and cooling it naturally to obtain a pre-oxidized hard carbon precursor; (2) Preparing a phosphorus-doped precursor: mechanically mixing the pre-oxidized hard carbon precursor obtained in step (1) with a phosphorus-containing dopant, and after mixing evenly, heating the mixture to 400-600°C at a heating rate of 2-10°C / min in a vacuum atmosphere and keeping the mixture warm for 2-8 hours, and then mechanically mixing the mixture with asphalt after naturally cooling, and after mixing evenly, heating the mixture to 400-600°C at a heating rate of 2-10°C / min under the protection of an inert gas and keeping the mixture warm for 2-8 hours, and then heating the mixture to 800-1000°C and keeping the mixture warm for 2-8 hours to obtain a phosphorus-doped precursor; wherein the mass of the phosphorus-containing dopant is 2-8% of the mass of the pre-oxidized hard carbon precursor, and the mass of the asphalt is 1-10% of the mass of the pre-oxidized hard carbon precursor; (3) preparing a catalyst precursor: adding the phosphorus-doped precursor obtained in step (2) to deionized water, adding a transition metal salt, the mass of which is 0.01-0.08% of the phosphorus-doped precursor, stirring for 6-72 hours, evaporating to dryness at 80° C., heating to 200-400° C. in an air atmosphere, and keeping the temperature for 1-3 hours to obtain a catalyst precursor; (4) preparing a hard carbon composite material: heating the catalyst precursor obtained in step (3) to 600-1200° C. in a mixed atmosphere of an inert gas and a carbon source gas for vapor deposition, keeping the temperature for 10-120 minutes, cooling naturally, and grinding thoroughly to obtain a hard carbon composite material; (5) Acid washing and purification: The hard carbon composite material obtained in step (4) is immersed in an acidic solution for 10-30 minutes, and then the immersed hard carbon composite material is washed with water until the pH is neutral to obtain a phosphorus-doped hard carbon composite material.

2. The method for preparing the phosphorus-doped hard carbon composite material for sodium battery according to claim 1, characterized in that: The D50 of the biomass raw material is 5-11 μm.

3. The method for preparing the phosphorus-doped hard carbon composite material for sodium battery according to claim 1, characterized in that: The biomass raw material is at least one of coconut shell, straw and starch.

4. The method for preparing the phosphorus-doped hard carbon composite material for sodium battery according to claim 1, characterized in that: The phosphorus-containing dopant is at least one of red phosphorus, sodium phosphate and ammonium phosphate.

5. The method for preparing the phosphorus-doped hard carbon composite material for sodium battery according to claim 1, characterized in that: The transition metal salt is at least one of copper nitrate, nickel nitrate, cobalt nitrate and iron nitrate.

6. The method for preparing the phosphorus-doped hard carbon composite material for sodium battery according to claim 1, characterized in that: The carbon source gas is at least one of benzene, toluene, xylene, ethanol, methane, ethylene and acetylene.

Citation Information

Cited By

  • Element-doped biomass hard carbon negative electrode material and preparation method thereof

    CN120622464A

  • Biomass-based sodium-ion battery hard carbon materials, their preparation methods and applications

    CN120664526B